Advances in 3D geo-information sciences - Kolbe, Thomas H.; Konig, Gerhard; Nagel, Claus; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
During the last decade developments in 3D Geoinformation have made substantial progress. We are about to have a more complete spatial model and understanding of our planet in different scales. Hence, various communities and cities offer 3D landscape and city models as valuable source and instrument for sustainable management of rural and urban resources. Also municipal utilities, real estate companies etc. benefit from recent developments related to 3D applications. To meet the challenges due to the newest changes academics and practitioners met at the 5th International Workshop on 3D Geoinformation in order to present recent developments and to discuss future trends. This book comprises a selection of evaluated, high quality papers that were presented at this workshop in November 2010. The topics focus explicitly on the last achievements (methods, algorithms, models, systems) with respect to 3D geo-information requirements. The book is aimed at decision makers and experts as well at students interested in the 3D component of geographical information science including GI engineers, computer scientists, photogrammetrists, land surveyors, urban planners, and mapping specialists.
Electronic reproduction.
Keywords: Three-dimensional imaging -- Geographic information systems; Three-dimensional imaging in geology; Electronic books